Effect of the rest interval duration between contractions on muscle fatigue - Nogueira Daniel V; Silva Sidney B; de Abreu Luiz; Valenti Vitor E; Fujimori Mahmi; de Mello Monteiro Carlos; Tortoza Charli; Ribeiro Wellington; Lazo-Osório Rodrigo A; Tierra-Criollo Carlos J (BioMedical Engineering OnLine, 2012)
Abstract Background We aimed to investigate the effect of rest interval, between successive contractions, on muscular fatigue. Methods Eighteen subjects performed elbow flexion and extension (30 repetitions) on an isokinetic dynamometer with 80º of range of motion. The flexion velocity was 120º/s, while for elbow extension we used 5 different velocities (30, 75, 120, 240, 360º/s), producing 5 different rest intervals (2.89, 1.28, 0.85, 0.57 and 0.54 s). Results We observed that when the rest interval was 2.89 s there was a reduction in fatigue. On the other hand, when the rest interval was 0.54 s the fatigue was increased. Conclusions When the resting time was lower (0.54 s) the decline of work in the flexor muscle group was higher compared with different rest interval duration.